A revision of Lophopappus (Asteraceae, Nassauvieae) - Katinas, Liliana; Sancho, Gisela; Vitali, Maira S. (Phytotaxa, 2013)
Lophopappus (Asteraceae, Nassauvieae) comprises five species endemic to South America. The genus is defined by its shrubby habit with unarmed branches, actinodromous or acrodromous leaf venation, solitary or few capitula at the apex of the branches with bilabiate and/or tubular-funnelform corollas, dorsally papillose style branches, and apically plumose pappus bristles. Leaf anatomy, cypsela trichomes, and pappus morphology are examined here for the first time in this genus. Lophopappus cuneatus is corroborated as a distinct species, L. berberidifolius is established as a synonym of L. tarapacanus, and a lectotype is designated for L. foliosus. A comprehensive key to the species and detailed descriptions, geographical distribution, phenology, illustrations and distribution maps are provided for all taxa.